2006
DOI: 10.1080/13645700600771942
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy treatment by laparoscopy, a short glimpse

Abstract: Ectopic pregnancy is a life-threatening emergency, the incidence of which is increasing globally. There are a number of factors predisposing to this condition; today, the most common of these is salpingitis. Due to advancements in diagnostic technology it is possible to diagnose this condition early and thus try to achieve a favourable outcome for the patient. Treatment options in the form of medical and surgical modalities are widely available. As minimally invasive therapy techniques are rapidly advancing, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…When these symptoms occur, primary treatment might be analgesics for pelvic pain, iron for anaemia, or even IVF for infertility. However, if this treatment is unsuccessful, surgery is always indicated [2729]. …”
Section: Discussionmentioning
confidence: 99%
“…When these symptoms occur, primary treatment might be analgesics for pelvic pain, iron for anaemia, or even IVF for infertility. However, if this treatment is unsuccessful, surgery is always indicated [2729]. …”
Section: Discussionmentioning
confidence: 99%
“…In 1997, Navarra et al (6) first reported "one-wound" laparoscopic cholecystectomy. At present, single-port laparoscopic surgery has been applied in ovarian cystectomy (7), salpingectomy (8,9), appendectomy (10,11), nephrectomy (12,13), Meckel's diverticulum excision (14), right hemicolectomy (15). From November 2008, we have succeeded in 33 cases of transumbilical single port laparoscopic cholecystectomy with a simple technique, the effect is satisfactory.…”
Section: Resultsmentioning
confidence: 71%
“…Ectopic pregnancy refers to pregnancies which occur out of uterus cavity and 98% of cases occur in the fallopian tube while another 2% occur in uncommon places such as the ovary, abdomen, caesarean scar and other [ 1 ]. The prevalence of ectopic pregnancies has increased from 0.5% in the last four decades to 2% in recent decades [ 1 3 ]. The rRupture of ectopic pregnancies leads to a high rate of mortality in mothers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%